Quality improvement and person-centredness: a participatory mixed methods study to develop the 'always event' concept for primary care. Issue 4 (28th April 2015) - Bowie, Paul; McNab, Duncan; Ferguson, Julie; de Wet, Carl; Smith, Gregor; MacLeod, Marion; McKay, John; White, Craig
Abstract : Objectives: (1) To ascertain from patients what really matters to them on a personal level of such high importance that it should 'always happen' when they interact with healthcare professionals and staff groups. (2) To critically review existing criteria for selecting 'always events' (AEs) and generate a candidate list of AE examples based on the patient feedback data. Design: Mixed methods study informed by participatory design principles. Subjects and setting: Convenience samples of patients with a long-term clinical condition in Scottish general practices. Results: 195 patients from 13 general practices were interviewed (n=65) or completed questionnaires (n=130). 4 themes of high importance to patients were identified from which examples of potential 'AEs' (n=8) were generated: (1) emotional support, respect and kindness (eg, "I want all practice team members to show genuine concern for me at all times"); (2) clinical care management (eg, "I want the correct treatment for my problem"); (3) communication and information (eg, "I want the clinician who sees me to know my medical history") and (4) access to, and continuity of, healthcare (eg, "I want to arrange appointments around my family and work commitments"). Each 'AE' was linked to a system process or professional behaviour that could be measured to facilitate improvements in the quality of patient care. Conclusions: This study is the first known attempt to develop the AE concept as a person-centred approach to quality improvement in primary care. Practice managers were able to collect data from patients on what they 'always want' in terms of expectations related to care quality from which a list of AE examples was generated that could potentially be used as patient-driven quality improvement (QI) measures. There is strong implementation potential in the Scottish health service. However, further evaluation of the utility of the method is also necessary.